On-body measure of reaction time correlates with intoxication level - Megan H. Blackwell; Henry L. Valk; Joshua Eaton; Samuel J. Kovaly; Samuel J. Karnes; Tue Vu; Kate M. Stevenson; Michael P. Kowalczyk; William B. Gormley (PLoS ONE, 2026)
Excessive alcohol use has profound effects on individual health and healthcare systems worldwide. Despite this, there is currently no system or device that can detect robustly the physiologic and functional effects of alcohol-based impairment in real-world conditions. A practical, on-body, device capable of rapidly and accurately determining the functional capacity of an individual to drive, before they can start the ignition of the automobile, is required. The goal of this pilot study was to evaluate the effect of acute alcohol intoxication on premotor time (PMT) and reaction time (RT), both highly sensitive of individual cognition, as evaluated by the Pison Technology wrist-worn wearable. Nineteen participants (9 male, 10 female) between the ages of 21 and 36 years were recruited for this study, including 14 subjects who consumed alcohol sufficient to raise blood alcohol concentration (BAC) to 0.10-0.12% within a 30-minute period and 5 controls who did not consume alcohol. Changes in reaction time data were correlated with blood alcohol levels as measured by breathalyzer testing, identifying a statistically significant difference between those participants under the legal limit and those over the legal limit (F(3, 3545) = 117, p < 0.001). The results indicated a significant effect of BAC level on reaction time change (Delta RT), Post hoc Tukey tests showed that participants in the medium (M = 104.4; 95% CI, 99.2--109.6) and high (M = 112.7; 95% CI, 107.5--117.9) BAC groups responded significantly slower than controls (M = 72.6; 95% CI, 69.9--75.3; p < 0.05 for both comparisons). The low BAC group (M = 67.5; 95% CI, 65.1--69.9) also differed from controls (p < 0.05). No significant difference was observed between the medium and high BAC groups (p = 0.13). Overall, reaction times increased as BAC levels rose. Both group and individual analyses confirmed that as the BAC increased in subjects, the PMT also increased. The PMT also decreased as the BAC returned to levels under the legal intoxication threshold (0.08%). The effect of BAC on PMT was significant, F(1, 2161) = 156, p < 0.001, with a partial η² of 0.067, indicating a moderate effect size, and a corresponding Cohen’s d of approximately 0.52, indicating a medium-sized difference between under-limit and over-limit conditions. This study demonstrated the first use case of an on-body, neuro-physiological sensor capable of detecting sensitive changes of reaction time, in real time, that serves as an easy-to-measure proxy for blood alcohol content and impairment.